Current Management of Type 1 Diabetes in Children: Guideline-based Expert Opinions and Recommendations - Şükrü Hatun; Tuğba Gökçe; Ecem Can; Elif Eviz; Kağan Ege Karakuş; Carmel Smart; Ragnar Hanas; Gül Yeşiltepe Mutlu (Galenos Yayincilik, 2024)
Successful management of type 1 diabetes (T1D) requires not only optimal glycemic outcomes, but also a holistic approach that encompasses all aspects of life and recommendations to address needs. Current goals include optimal glycemic values, quality of life and life expectancy similar to peers, prevention of long-term complications, prevention of severe hypoglycemia as far as possible and facilitation of glucose management. The International Society for Pediatric and Adolescent Diabetes (ISPAD) has been updating its guidelines for diabetes care every four years since 1995, covering more and more topics. For optimal metabolic outcomes, diabetes teams need to follow these current recommendations, adapt them to their clinical practice and provide guidance to people with T1D and their families. In this review, in the light of ISPAD 2018-2022 guidelines and clinical experiences, "10 Key Recommendations", emphasizing the importance of teamwork and the use of technology, current T1D treatment is described for practical applications.